The Effect of Using Technology-Enhanced English Course (TEEC) in Teaching English as ‎a Foreign Language at Preparatory Schools - Ali, Nadhim (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to explore the impact of the Technology-Enhanced English Course (TEEC) on teaching English as a foreign language at preparatory schools in Iraq. The sample was selected randomly, and its size consisted of 44 English teachers enrolled in the study. The findings showed that the majority of the different teachers highlighted the importance of active learning-based technology in teaching English as a foreign language to learn and process new things to make students more likely to engage in the target language. Therefore, the relationship between the traditional teaching and the technology-enhanced course was significant (p < 0.09); the t-test is 6.859, df is 86 with a mean of 3.06 and SD 0.474 for technology teaching and a mean of 2.22 and SD 6.66 for traditional teaching at preparatory schools in Iraq. The study recommends that English teachers should use active learning-based technology services to foster the learning process and widen their students’ knowledge by adopting the technology-enhanced courses in the class by the technological requirements to learn a new language. The findings of this study have several important implications for further studies in teaching English as a foreign language.